ANALISIS KAPASITAS RESERVOIR DALAM PEMENUHAN KEBUTUHAN AIR PADA KELURAHAN PADANG TEMU - Barrorotul Azizah (Jurnal Ilmiah BERING, 2022)
Reservoir is a water storage building before distribution to customers or the public which can be placed underground or above ground in the form of a tower or towers Clean water management in Temu Karya , Padang Temu Village. Managed by the residents of Temu Karya. The Padang Temu Village Reservoir has a capacity/volume of 535.07303 m3 which is sourced from a spare spring. The research aims to determine whether the current reservoir capacity is still able to meet the increasing demand for clean water throughout the year based on population projections from 2022-2031. The population of Temu Karya in 2022 will be 545 people. The results of the projected population until 2031 are 686.5495 people using the linear arithmetic method. The current reservoir in Padang Temu Village is sufficiently capable of serving the community optimally for 24 hours, because water can be flowed continuously. Based on this study it can be concluded that a reservoir measuring (9.72 x 9 x 7 m) is sufficient water, and if in the following years there is a shortage of water capacity, the residents of the Padang Temu Village must look for new sources of water to overcome the shortage of clean water caused by a significant population growth.